The relation between estrogen level, anti-Ro (SSA), anti-La (SSB) & secondary Sjogren's syndrome patients - Mustafa Al-Ahmad, Basma Ezzat; Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon; Khalil, Raida W. (EuroJournals Publishing, 2009)
Secondary Sjogrens syndrome (sSs) is one of the autoimmune diseases that are covered by a big term Rheumatoid Arthritis (RA). Estrogen level was measured for both secondary Sjogren`s syndrome (sSs) and control females, anti Ro (SSA) & anti La (SSB) tests were also measured for sSs patients. the aim of this study was to find out the relation between the elevation in estrogen level and one of the serious autoimmune diseases which is Ss especially in the secondary type (in the presence of the positive results of SSA &SSB) and to clarify the reason of the high incidence of this disease in female than in male. Twenty nine females patients age range (25-40) suffering from sSs and twenty control(healthy females age between 20-35) were involved in this study. This study showed that estrogen level was significantly higher (p≤0.01) in sSs patients comparing to normal control group, with higher percentage of positive results in anti-Ro (SSA) compared to anti- La (SSB). Increase of estrogen level in sSs female may be the explanation of high incidence of sSs in females. Accordingly, Anti-Ro cause antibodies are more specific to sSs patients than anti- La.